Disruption of Corroded Rod with Piecewise Constant Thickness under Dynamic Longitudinal Loading - I.A. Akhoundova (Механика машин, механизмов и материалов, 2009)
The present paper considers longitudinal oscillations of corroded rod with piecewise constant thickness taking initial stress into account. The value of proper frequency is defined. In addition, the value of the frequency when the rod breaks in the place of connection of rod elements is defined.